(untitled) (LACCEI, 2024)
The objective of this investigation was to determine and compare the values of maximum equivalent stresses according to the von-Mises(vM) criteria of a post-die restoration in an incisor tooth, using the mechanical properties of two types of materials (fiberglass , NiCr alloy) and 4 chew type force values (100, 150, 200 and 250) N the stress calculation carried out was of a static type, this was carried out using the ANSYS software. In the case of the crown, the data on the properties of lithium disilicate (IPS e.max CAD) were used in addition to this, the properties of the materials corresponding to dentin and periodontium were also used. The first stage of the process The simulation consisted in the acquisition of the 3D model of an incisor tooth, through a scanning process to later reduce the number of elements and perform the smoothing, the Meshmixer software was used, the final file was exported to ANSYS, where all the parts of the tooth considering the recommendations of an endodontic process for the simulation, the chewing forces were applied in an area of 2 mm2, taking into account an angle of 45° with respect to the longitudinal axis of the tooth in addition, the stress results of the restored teeth with the incisor tooth without any type of restoration From the results of the numerical evaluation we can conclude that the post-type restoration stump n that uses fiberglass would have greater chances of success, since the values of equivalent stress are lower compared to when the NiCr alloy is used this is 28.8 MPa and 141.53, respectively for the force of 250 N however, the stress state of the material used as cement (adhesive), in the case of the fiberglass stump post is higher compared to the case that uses the NiCr alloy.